06 Horizontal Reflection

Jason Lee


Move the slider for a in the applet and answer the following questions based on your observations.

y = eˣ + 1 vs y = e⁻ˣ +1

Question 6.1

How do we obtain the graph of y = e⁻ˣ +1 from the graph of y = eˣ + 1?

Question 6.2

The equation y = e⁻ˣ +1 can be seen as replacing the variable x in the equation y = eˣ + 1 by the variable _____.

Question 6.3

What can be said about the y-intercepts of both curves?

Question 6.4

What can be said about the horizontal asymptotes of both curves?